Manganese(III) acetate mediated oxidative radical cyclizations. Toward vicinal all-carbon quaternary stereocenters. - Logan, A; Parker, J; Hallside, MS; Burton, J (2012)
Manganese(III) acetate mediated oxidative radical cyclizations have been used to synthesize a range of densely functionalized and sterically congested cyclopentane-lactones. A number of the resulting lactones contain vicinal all-carbon quaternary stereocenters adjacent to a tertiary benzylic stereocenter and are formed with high levels of stereocontrol.